The impact of jurisprudential rules on the ruling of aborting a deformed fetus - aksa, saida; kettab, haiat (Journal of Social Sciences and Humanities, 2025)
The issue of aborting a fetus, regardless of the reason, has been a topic extensively discussed by Islamic jurists, both past and present. They unanimously agree that it is forbidden to abort a fetus after it has been endowed with a soul, except in one specific case—when continuing the pregnancy poses a real danger to the mother’s life. In recent times, many scholars and researchers have applied ijtihad (independent legal reasoning) to medical issues, including the application of jurisprudential rules to the abortion of deformed fetuses. This research seeks to highlight some of those rules that govern the abortion of deformed fetuses, with the aim of fulfilling the objectives of Islamic law in preventing harm and ensuring benefit to the individuals accountable under Shariah. Our findings indicate that the jurisprudential texts affirm the prohibition of harming the fetus, whether healthy or deformed, except in one circumstance. Furthermore, modern medical technology often detects deformities that are minor and can be lived with, while more severe deformities typically lead to natural miscarriage or the fetus dying shortly after birth. Additionally, the application of jurisprudential rules to contemporary issues follows specific guidelines that must be observed.